Multi-responses Methodology Applied in the Electroanalytical Determination of Hair Dye by Using Printed Carbon Electrode Modified with Graphene - Hudari, Felipe Fantinato [UNESP]; CostaFerreira, Sergio Luis; Zanoni, Maria Valnice Boldrin [UNESP] (Wiley, 2016)
This paper describes a rapid and sensitive method for determination of the hair dye Basic Blue 41 in wastewater samples using screen-printed carbon electrodes modified with graphene (SPCE/Gr). The method is based on the reversible reduction of azo groups of the dye at potential of -0.23V/-0.26V, where both the anodic and cathodic currents increased 1,300% when compared to screen-printed carbon (SPCE) and glassy carbon electrodes (GCE). The optimization of a square wave voltammetric method was performed by means of 23 factorial design, Doehlert matrix and multi-response assays, and the best parameters were: frequency (54.8Hz), step potential (6mV), pulse amplitude (43.7mV) and pH4.5. The analytical curve was constructed from 3.00×10-8 to 2.01×10-6molL-1, with detection and quantification limits of 5.00×10-9 and 1.70×10-8molL-1, respectively. The repeatability of the method evaluated for 10consecutive measurements at concentrations of 1.70×10-7molL-1 and 1.70×10-6molL-1, showed relative standard deviation of 3.56 and 0.57 %, respectively. The sensor based in SPCE/Gr was successfully applied in wastewater samples collected from a drinking water treatment plant and validated by comparison with HPLC-DAD method with good accuracy.
Keywords: Basic blue 41 dye; Factorial design; Graphene; Screen-printed carbon electrode; Voltammetric sensor for hair dye